Capital flight from Indonesia and the Philippines. - Lim, Poh Guan. (2010)
Capital flight refers to the large-scale financial capital outflow from a country. Such largescale financial outflows are usually triggered by fears and suspicions about the country's future and currency exchange rate. By and large, it involves the flow of productive resources from poor (developing) to rich countries. This creates a foreign-debt problem for developing countries. In this report, indicative estimates of the amount of capital flight from Indonesia and the Philippines from 1986 to 1995 are provided. The authors adopted two different approaches to estimating capital flight. The first is a direct method known as the Balance of Payment method and the second is an indirect method known as the Residual method. Estimates obtained using both methods were fine-tuned by adjusting for mis-invoicing data, necessary ownership of foreign assets and incomplete debt data. The correlation of currency devaluation, inflation, interest rates and political climate to capital flight was then evaluated.